Modelling potential areas of groundwater development for agriculture in northern Ghana using GIS/RS - Forkuor, Gerald; Pavelic, Paul; Asare, E.; Obuobie, Emmanuel (Informa UK Limited, 2013)
Groundwater development potential in northern Ghana (108 671 km2) has been assessed by combining spatial layers for five critical factors?recharge rate, regolith thickness, transmissivity, borehole success rate and static water level?through a multi-criteria analysis approach to rank development potential from the viewpoint of groundwater availability and accessibility at a resolution of 1 km2. The results indicate a high potential for development in the study area, as about 70% of the area was found to have high to moderate groundwater availability, while 83% has high to medium groundwater accessibility. Comparing the two main hydrogeological environments, the Precambrian Basement rocks (PCB) area was found to generally have a higher groundwater development potential than the Voltaian Sedimentary rocks (VSB). More detailed investigation revealed that the VSB can produce a small proportion of exceptionally high-yielding boreholes that can support large-scale irrigation. A test of the reliability of results showed that generally, the majority of high- and low-yielding boreholes fall in areas predicted by the model as having high and low groundwater availability, respectively.